If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(3x + 1) = 28 Reorder the terms: 2x(1 + 3x) = 28 (1 * 2x + 3x * 2x) = 28 (2x + 6x2) = 28 Solving 2x + 6x2 = 28 Solving for variable 'x'. Reorder the terms: -28 + 2x + 6x2 = 28 + -28 Combine like terms: 28 + -28 = 0 -28 + 2x + 6x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-14 + x + 3x2) = 0 Factor a trinomial. 2((-7 + -3x)(2 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-7 + -3x)' equal to zero and attempt to solve: Simplifying -7 + -3x = 0 Solving -7 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = 0 + 7 -3x = 0 + 7 Combine like terms: 0 + 7 = 7 -3x = 7 Divide each side by '-3'. x = -2.333333333 Simplifying x = -2.333333333Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-2.333333333, 2}
| xy+30y-30=0 | | 5x^(1/3)-x^(2/3)-54=0 | | -8r-7=24 | | 20(-1/2) | | 1/5(2x+9)=2(1-2x)+13 | | 190=-7x-5(5x-6) | | -8(1+6n)=-344 | | 1/15r=41/2 | | -3x+7(x+4)=68 | | (-7/11)(-11) | | -1/6+(-5/8) | | 108=-5x-3(-5x-16) | | -15-4=9-8x | | 2b^2-6b-20=0 | | 7(1+2n)=119 | | 2msquared-11m+14=0 | | 6x-2y=24 | | 9x-9=-2x-11 | | 4n^2+12n-16=0 | | -5(1+1x)=15 | | 95=2x-5(-3x+15) | | 4n^2-14x+24=0 | | F(x)=x^2-5x-24 | | 9/2x=-18 | | 7x+8=x+62 | | 3n^2+18n+24=0 | | 4(x-3)-5(x-2)=7(3x-1)+29 | | a^2=3a-10 | | -146=3x-2(-5x+8) | | x=1/2(180-x)+6 | | 22+8= | | 4b^2-8b+4=0 |